2021
DOI: 10.1002/aur.2629
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the interrelations between the autism polygenic score and psychiatric family history in risk for autism

Abstract: Psychiatric family history or a high autism polygenic risk score (PRS) have been separately linked to autism spectrum disorder (ASD) risk. The study aimed to simultaneously consider psychiatric family history and individual autism genetic liability (PRS) in autism risk. We performed a case-control study of all Denmark singleton births, May 1981-December 2005, in Denmark at their first birthday and a known mother. Cases were diagnosed with ASD before 2013 and controls comprised a random sample of 30,000 births … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…In our sample, autism PGS explained 1.8% of the variance in autism diagnostic status, which is somewhat lower than in the original GWAS, and furthermore, autism PGS was not significantly higher in individuals with autism diagnosis compared to those without (p = 0.46) in our study population, indicating low power. However, other studies based on the same discovery GWAS also found that autism PGS was only weakly related or even unrelated to autism diagnosis and psychiatric family history of autism (Jansen et al, 2020;Schendel et al, 2022). That rare genetic variants play an important role in the aetiology of autism (Geschwind & ZHANG ET AL.…”
Section: Autism Pgs and Ed Severitymentioning
confidence: 99%
“…In our sample, autism PGS explained 1.8% of the variance in autism diagnostic status, which is somewhat lower than in the original GWAS, and furthermore, autism PGS was not significantly higher in individuals with autism diagnosis compared to those without (p = 0.46) in our study population, indicating low power. However, other studies based on the same discovery GWAS also found that autism PGS was only weakly related or even unrelated to autism diagnosis and psychiatric family history of autism (Jansen et al, 2020;Schendel et al, 2022). That rare genetic variants play an important role in the aetiology of autism (Geschwind & ZHANG ET AL.…”
Section: Autism Pgs and Ed Severitymentioning
confidence: 99%
“…Nine studies assessed the association between the autism polygenic score and autism diagnosis. Of these, seven reported a significant positive association 10,25,27,30,32,33,36 . Two studies, based on smaller samples than the ones that reported significant associations, reported no significant association 37,50 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, based on smaller samples than the ones that reported significant associations, reported no significant association 37,50 . In addition, the autism polygenic score acted in a dose-dependent manner, where people in higher percentiles on average were more likely to be diagnosed with autism 10,36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2022 U.S. survey found a 2.6% prevalence rate among Spanish-speaking families ( 37 ). Saito et al reported a prevalence of 3.22% for Japan ( 38 ), and Schendel et al reported that a lifetime incidence of autism in a Danish cohort ranged from 3.52 to 4.28% ( 39 ). By contrast, schizophrenia prevalence was 0.33% before 1990, and 0.51% after 2013 ( 40 ).…”
Section: The Extent Of Autism Heterogeneitymentioning
confidence: 99%